Kemampuan Berpikir Kreatif Siswa dalam Menyelesaikan Masalah Open-Ended Ditinjau dari Gaya Belajar - Husniyah, Hana Kholifatul; Sa'dijah, Cholis (International Journal of Progressive Mathematics Education, 2025)
Purpose: This research aims to describe students' creative thinking abilities in solving open-ended problems viewed from the perspective of learning styles to support the essential competencies required in the 21st century. Design/methodology/approach: This study utilizes a qualitative approach where data collection was conducted through creative thinking ability tests, learning style assessments, and interviews. The research subjects consisted of 33 tenth-grade students from a senior high school in Malang. Interviews were conducted with subjects from each learning style, ensuring a proportional representation of visual, auditory, and kinaesthetic styles while considering students' communication skills, utilizing instruments that were validated through expert judgment. Findings: Based on the research results, it was found that students with a visual learning style met the criteria for flexibility and novelty. Auditory learners fulfilled the criteria for fluency and flexibility. Conversely, kinaesthetic learners did not meet the criteria for fluency, flexibility, or novelty. Practical implications: Creative thinking skills can be cultivated in students through open-ended problem-solving instruction because learning styles significantly influence an individual's creative thinking capacity. Originality/value: This study provides a specific overview of creative thinking as a fundamental skill for the 21st century based on an analysis of learning styles in the context of solving open-ended problems.   Purpose: Penelitian ini bertujuan untuk mendeskripsikan kemampuan berpikir kreatif siswa dalam menyelesaikan masalah open-ended ditinjau dari gaya belajar guna mendukung kemampuan yang dibutuhkan di abad 21. Design/methodology/approach: Pendekatan penelitian ini adalah kualitatif di mana pengumpulan data dilakukan melalui tes kemampuan berpikir kreatif, tes gaya belajar, dan wawancara. Subjek penelitian adalah 33 siswa kelas X yang berasal dari salah satu sekolah menengah atas di Kota Malang. Wawancara dilakukan pada subjek di setiap gaya belajar dengan memperhatikan proporsional gaya belajar visual, auditorial, dan kinestetik serta kemampuan komunikasi siswa menggunakan instrumen yang valid melalui proses validasi ahli. Findings: Berdasarkan hasil penelitian diperoleh bahwa siswa bergaya belajar visual memenuhi fleksibilitas dan kebaruan, siswa auditorial memenuhi kefasihan dan fleksibiltas, dan siswa kinestetik tidak memenuhi kefasihan, fleksibilitas, dan kebaruan. Practical implications: Kemampuan berpikir kreatif dapat dibelajarkan kepada siswa melalui pembelajaran penyelesaian masalah open-ended karena gaya belajar dapat mempengaruhi kemampuan berpikir kreatif seseorang. Originality/value: Penelitian ini memberikan gambaran spesifik mengenai kemampuan berpikir kreatif sebagai bagian dari kemampuan yang dibutuhkan di abad 21 berdasarkan tinjauan gaya belajar dalam menyelesaikan masalah open-ended.